HUBUNGAN PENGAWASAN YANG DILAKUKAN PIMPINAN DENGAN KEPUASAN KERJA PEGAWAI PADA KANTOR BADAN KEPEGAWAIAN DAERAH PROVINSI SUMATERA BARAT - Deby Avri Elvi Dhona (Universitas Negeri Padang, 2015)
The purpose ofthis study was to determine the relationship of supervision conducted leadership and job satisfaction of employees at the Office ofthe Regional Employment Boardof West Sumatra Province. Population of this study amounted to 76 and 47 samples using the formula Proportional Stratified Random Sampling Technique. The instrument of this reseach is using statement with linkert scale model to see the validitiy and reliability with analysis data mean score. From this study can be seen that the supervisory relationship with the leadership's job satisfaction of employees on staffing agency office area west Sumatra provinceis quite good.Key Word : supervision and job satisfaction